Membaca Takdir Televisi Lokal Wala Yahya Wala Yamut - Abdullah Khusairi (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2012)
The mass media has two sides of currency, which is between idealistic and commercial. Basically both walked like two rails. If the idealistic built properly, it will offset the commercial side with the assumption, the viewers will come 'donate' ad for aspiration and inspiration channeled in every program they broadcast. Worth watching, educational, informative, entertaining too, is an inviting 'the cake' on the television. The presence of local television expected, at most, ten local public interest where the television can be channeled. Since there may be hope on the national private television that have been "busy" with programs about "Jakarta"